2014
DOI: 10.1902/jop.2014.130455
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol, an Anticaries Agent, Exhibits Potent Inhibition of Inflammatory Responses in Human THP‐1‐Derived Macrophages Infected With Porphyromonas gingivalis

Abstract: Background Xylitol is a well-known anticaries agent and has been used for the prevention and treatment of dental caries. In this study, the anti-inflammatory effects of xylitol are evaluated for possible use in the prevention and treatment of periodontal infections. Methods Cytokine expression was stimulated in THP-1 (human monocyte cell line)-derived macrophages by live Porphyromonas gingivalis, and enzyme-linked immunosorbent assay and a commercial multiplex assay kit were used to determine the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…The authors of the present study reported on the anti‐inflammatory effect of xylitol suppressing IL‐1β and TNF‐α expression induced by P. gingivalis LPS in RAW 264.7 cells and the inhibitory effect on P. gingivalis growth 23 . Xylitol inhibited: 1) growth; 2) metabolism; and 3) polysaccharide production of mutans streptococci 22 , 24 . It was also recently found that xylitol inhibited IL‐1β and TNF‐α production through inhibition of internalization and phagocytosis of live P. gingivalis into differentiated THP‐1 macrophages and attachment of P. gingivalis to the surface of differentiated THP‐1 macrophages 24 .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The authors of the present study reported on the anti‐inflammatory effect of xylitol suppressing IL‐1β and TNF‐α expression induced by P. gingivalis LPS in RAW 264.7 cells and the inhibitory effect on P. gingivalis growth 23 . Xylitol inhibited: 1) growth; 2) metabolism; and 3) polysaccharide production of mutans streptococci 22 , 24 . It was also recently found that xylitol inhibited IL‐1β and TNF‐α production through inhibition of internalization and phagocytosis of live P. gingivalis into differentiated THP‐1 macrophages and attachment of P. gingivalis to the surface of differentiated THP‐1 macrophages 24 .…”
Section: Discussionmentioning
confidence: 59%
“…Xylitol is a widely used anticaries agent because it is not fermented by Streptococcus mutans 22 , 24 , 50 . The authors of the present study reported on the anti‐inflammatory effect of xylitol suppressing IL‐1β and TNF‐α expression induced by P. gingivalis LPS in RAW 264.7 cells and the inhibitory effect on P. gingivalis growth 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xylitol, a naturally occurring a low-calorie pentose sugar substitute, is known for its ability to suppress growth and metabolism of cariogenic mutans streptococci in particular [45]. However, a little known effect of xylitol is its ability to launch an anti-inflammatory response in macrophages infected with the periodontopathogen P gingivalis [46,47]. Shimauchi et al [31] evaluated this phenomenon, and they did not find any significant improvement in clinical parameters of periodontitis between the control group (placebo + xylitol) and the test group (probiotic + xylitol).…”
Section: Discussionmentioning
confidence: 99%